2021
DOI: 10.1002/car.2723
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a Sexual Abuse Prevention Programme in the First‐Grade Indonesian Curriculum to Improve Children's Self‐Protection

Abstract: The purpose of this article is to analyse the effect of the School‐Based Child Sexual Abuse Prevention Programme (Program Prevensi Pelecehan Seksual Berbasis Sekolah (P3SBS)) on first‐grade primary school students' ability to protect themselves from sexual abuse. The study was conducted in two primary schools in Surakarta, Indonesia. Fifty‐five students participated in the P3SBS and 55 participants were in the control group. The pre‐test and post‐test of the control group were designed to test the effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Video media can present moving images and sounds that can attract children's attention and make it easier for children to understand sexual education materials. Two researchers combine video media and leaflets [41]; video media, games, and dolls [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Video media can present moving images and sounds that can attract children's attention and make it easier for children to understand sexual education materials. Two researchers combine video media and leaflets [41]; video media, games, and dolls [17].…”
Section: Resultsmentioning
confidence: 99%
“…Differences in effectiveness values indicate a reduced risk of sexual abuse of children. The increase in knowledge Comic [40,54,55,58,63] Leaflet [41] Origami [61] Game [17,45]- [47,52] Videos [17,41]- [44,59,60] and skills is marked by changes in behavior in life, reducing the risk of child sexual abuse.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Czerwinski et al (2018) found that the IGEL prevention program used to prevent child sexual abuse led to an increase in knowledge and action plans related to CSA in children in the intervention group. According to Wulandari et al (2022) Parents need to be knowledgeable to give prevention education to their children (Apaydın Cırık et al, 2020;Apaydın Cırık et al, 2022;Tunç et al, 2018;Zhang et al, 2020). Based on the child sexual abuse knowledge and attitude scores of the fathers in this study, their knowledge/attitude about child sexual abuse is below the moderate level.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini bertujuan untuk membekali pengetahuan pada anak mengenai memahami cara merawat organ tubuh, nama-nama anggota tubuh dan mengetahui cara mencegah serta memecahkan masalah ketika seorang anak mengalami dirinya merasa tidak anyam karena perilaku atau tingkah laku orang lain. Keterlibatan orang tua dan guru membuat topik dan metode lebih banyak luas (Wulandari et al, 2022). Upaya yang dilakukan adalah penggunaan papan bimbingan sebagai media pencegahan pelecehan seksual.…”
Section: Hasil Dan Pembahasanunclassified